The Effect of Organic and Anorganic Fertilization on VFA and N-NH3 Production of Rice Straw of Pandan Wangi Variety In - Vitro - Maalina, Rizky Ayu; Bata, Muhamad; Rahayu, Sri (ANGON: Journal of Animal Science and Technology, 2020)
Background. The purpose of this study was to assess the ability of Pandan Wangi rice straw varieties resulting from organic and inorganic fertilizers to produce rumen fermentation products in the form of Volatile Fatty Acid (VFA) and ammonia nitrogen (N-NH3). Materials and methods. The material used in this study was rumen fluid from 3 beef cattle taken from the Bantarwuni Slaughterhouse, Kembaran District, Banyumas Regency immediately after the cows were slaughtered. The samples tested came from 2 fields, namely land A using organic fertilizers and land B using inorganic fertilizers. Samples were taken as many as 20 points in one rice field at random, then the samples were dried using an oven. The method in this study was an invitro experiment with the research design used was the independent T test. Results. The results showed that there was no difference (P> 0.05) on the production of VFA and N-NH3 in Pandan Wangi rice straw varieties resulting from organic and inorganic fertilizers. Conclusion. Rumen fermentation products in the form of VFA and N-NH3 fed with Pandan Wangi rice straw did not depend on the type of fertilization.